Heart development and regeneration - Rosenthal, Nadia; Harvey, Richard P. (Elsevier/Academic, 2010)
The development of the cardiovascular system is a rapidly advancing area in biomedical research, now coupled with the burgeoning field of cardiac regenerative medicine. A lucid understanding of these fields is paramount to reducing human cardiovascular diseases of both fetal and adult origin. Significant progress can now be made through a comprehensive investigation of embryonic development and its genetic control circuitry. Heart Development and Regeneration, written by experts in the field, provides essential information on topics ranging from the evolution and lineage origins of the developing cardiovascular system to cardiac regenerative medicine. A reference for clinicians, medical researchers, students, and teachers, this publication offers broad coverage of the most recent advances. Volume One discusses heart evolution, contributing cell lineages; model systems; cardiac growth; morphology and asymmetry; heart patterning; epicardial, vascular, and lymphatic development; and congenital heart diseases. Volume Two includes chapters on transcription factors and transcriptional control circuits in cardiac development and disease; epigenetic modifiers including microRNAs, genome-wide mutagenesis, imaging, and proteomics approaches; and the theory and practice of stem cells and cardiac regeneration. Authored by world experts in heart development and disease New research on epigenetic modifiers in cardiac development Comprehensive coverage of stem cells and prospects for cardiac regeneration Up-to-date research on transcriptional and proteomic circuits in cardiac disease Full-color, detailed illustrations.